Analisis Kompensasi Dan Lingkungan Kerja Terhadap Prestasi Kerja Karyawan Pada PT. Pelindo I (Persero) - Febrilian Lestario (ARBITRASE: Journal of Economics and Accounting, 2022)
This study aims to determine and analyze the positive and significant effect of compensation and work environment on employee work performance at PT Pelindo I (Persero) both partially and simultaneously. This research uses quantitative methods with the data analysis technique used, namely multiple linear regression. The sample in this study was 64 respondents with sample determination using purposive sampling techniques. The results showed that: (1) The compensation variable has a calculated t value (6.594) > t table (1.67022) and a sig level (0.000) < 0.05 which means that the job training variable (X1) partially has a positive and significant influence on the work performance (Y) of employees at PT Pelindo I (Persero). (2) The work environment variable has a calculated t value (3.459) > t table (1.67022) and significance (0.001) < 0.05 which means that the work environment variable (X2) partially has a positive and significant influence on the work performance (Y) of employees at PT Pelindo I (Persero). (3) The compensation variable and work environment have a calculated F value (51.883) > F table (3.15) with a sig level (0.000) < 0.05 which means that the compensation variable (X1), and the work environment (X2) simultaneously have a positive and significant influence on the work performance (Y) of employees at PT Pelindo I (Persero), (4) while the magnitude of the influence exerted by independent variables on dependent variables is 61.8%. While the remaining 38.2% was influenced by other factors outside this study.